Revisiting Japanese Food Consumption Patterns - Alias, Abdullah; Kobayashi, Hajime; Matsumura, Ichizen; Hassan, Maizom; Mustapa, Zakaria; Md Akhir, Md Nasrudin; Paidi, Rohayati; Hassan, Asmadi; Mohd Huda, Mohd Ikbal (WILAYAH: The International Journal of East Asian Studies, 2011)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.